Comparison of Serum Triglyceride and Cholesterol Levels in Premature Neonates with or without Respiratory Distress Syndrome (RDS) - Roya Kelishadi; Behzad Barekatain; Atefeh Fatahi (International Journal of Pediatrics)
Background. Deficiency or reduced transmission of long-chain fatty acids and essential fatty acids may inhibit lung growth and development. We aimed to evaluate and compare serum triglyceride and cholesterol levels in premature neonates with RDS. Methods. This study is a cross-sectional study performed on premature neonates born in Beheshti Hospital in Isfahan in 2018. Immediately after birth and after umbilical cord clumping, blood samples were taken from the umbilical artery and triglyceride and total cholesterol levels were measured. Those patients with the diagnosis of RDS were transferred to the neonatal intensive care unit (NICU). Data regarding the laboratory results of the lipid profile in patients were compared to that in the other group. Results. A total number of 100 neonates entered the study and were divided into 2 groups. Analysis of gender and mean gestational ages among the two groups showed no significant differences between the groups (P=0.84 and P=0.28, respectively). Further analysis showed a significant decreased serum cholesterol in the group 1 of patients (P=0.01), but there were no significant differences between the two groups regarding triglyceride levels (P=0.43). There was a significant direct relationship between gestational age and serum triglyceride levels in patients with RDS (r=0.550, P<0.001). Conclusion. Here, we indicated significantly lower cholesterol levels in the cord serum of premature neonates with RDS compared to non-RDS premature neonates. Our data also showed a significant direct relationship between gestational age and serum triglyceride levels in patients with RDS. These data were in line with the previous studies.